Prática de ensino supervisionada em ensino de Educação Musical no Ensino Básico - Ramalhoto, Paulo Estefânio da Costa (2013)
Este relatório incide sobre a Prática de Ensino Supervisionada levada a cabo no Agrupamento de Escolas de Pedome no ano letivo 2012/2013 no âmbito do mestrado em Ensino de Educação Musical no Ensino Básico. Reflete sobre a importância da música no desenvolvimento da criança, sobre as teorias do ensino da música, as orientações curriculares da tutela e sobre os estilos docentes, realçando o estilo autoritativo. Assente neste quadro teórico e conceptual, reflete sobre as Experiências de Ensino/aprendizagem desenvolvidas no estágio. This report focuses on the Supervised Teaching Practice's carried out in the School Grouping in Pedome, in the academic year of 2012/2013, under the master's degree in Teaching Musical Education in the Basic School. Reflects upon the importance of music in the human development, upon the music education theories, the curricular guidelines from ministry coordination and upon the teaching styles, enhancing the authoritative style. Based on this theoretical and conceptual framework, it reflects upon the Teaching and Learning Experiences developed in the internship. institution in the hosting regions. To achieve that, we used the traditional or economic-base approach and the skill-base approach. From the traditional approach, based in the Caffrey and Isaacs’s impact model, we obtained the direct economic impact of the IPB. From the skill-base approach we are currently estimating the human capital that is directly linked to the IPB. We expect to determine the total economic impact of the IPB and how a change in its local demand will affect the economy of the surrounding regions, and also what is the higher education institutions’ impact on the individuals and how it will affect their lifelong earnings.